Re-188 Enhances the Inhibitory Effect of Bevacizumab in Non-Small-Cell Lung Cancer - Jie Xiao; Xiaobo Xu; Xiao Li; Yanli Li; Guobing Liu; Hui Tan; Hua Shen; Hongcheng Shi; Dengfeng Cheng (Molecules, 2016)
The malignant behaviors of solid tumors such as growth, infiltration and metastasis are mainly nourished by tumor neovascularization. Thus, anti-angiogenic therapy is key to controlling tumor progression. Bevacizumab, a humanized anti-vascular endothelial growth factor (VEGF) antibody, plus chemotherapy or biological therapy can prolong survival for cancer patients, but treatment-related mortality is a concern. To improve inhibitory effect and decrease side-effects on non-small-cell lung cancer (NSCLC), we used Re-188, which is a β emitting radionuclide, directly labeled with bevacizumab for radioimmunotherapy in a human A549 tumor model. Cytotoxic assay data showed that, after 188ReO4− or 188Re-bevacizumab at different concentration for 4 and 24 h, a time- and radioactivity does-dependent reduction in cell viability occurred. Also, an apoptosis assay conformed great apoptosis in the 188Re-bevacizumab group compared with controls and other treatment groups. In vivo, tumor volumes in the 188Re-bevacizumab (11.1 MBq/mice) group were not reduced but growth was delayed compared with other groups. Thus, 188Re-bevacizumab enhanced the therapeutic effect of bevacizumab, suggesting a potential therapeutic strategy for NSCLC treatment.